SISTEM WIND-DIESEL UNTUK PEMBANGKIT LISTRIK DI LOKASI DENGAN KECEPATAN ANGIN MENENGAH DI INDONESIA - Sahat Pakpahan (National Institute of Aeronautics and Space - LAPAN, 2006)
Windspeed is used as a reference in utilization of windturbine as a generating system and will be the main variable for calculation of the energy produced at a certain location. Windspeeds are classified in small scale, medium and large scales. Applications of small scales are generally in the stand-alone mode, while the large systems are intended for interconnection into the utility grid. In between, there are medium scale applications with the annual average windspeed of 4.0 m/s - 50 m/s. Examples of applications are hybrid of windturbine with local diesel generating sets, known as wind-diesel system using one or more windturbines of the size of 10 kW-100 kW and to be matched with the capacity of the existing deisel. most applications are in the intermittent mode of operation in order to obtain higher fuel saving which is used to operate the diesel. Some configurations, selection of components, modelling and calculations are presented to identify more detailed behaviour of the system. Keywords: Angin-diesel, Modus bergantian, Penghematan bahan bakar.